THE INFLUENCE OF INFORMATION TECHNOLOGY UTILIZATION, WORK EXPERIENCE, SKILLS, AND INCENTIVES ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS AT THE BADAN PUSAT STATISTIK (BPS) OF WEST NUSA TENGGARA PROVINCE - Widowati, Syagita Dimesia; Lestari, Baiq Anggun Hilendri; Agustiningsih, Wulandari (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
In the current digital era, information systems play a crucial role in the operations and decision-making processes of organizations. This study aims to examine the influence of information technology utilization, work experience, skills, and incentives on the effectiveness of accounting information systems at Badan Pusat Statistik (BPS) of West Nusa Tenggara Province. The primary focus of this research is to identify how these factors contribute to the effectiveness of accounting information systems. The study employs a quantitative method, using primary data collected through questionnaires. The data analysis method used is multiple linear regression (PLS-SEM) with SmartPLS 4 software. The results indicate that the variables of work experience, skills, and incentives have a positive and significant impact on the effectiveness of accounting information systems, while the utilization of information technology has a negative and significant effect on the effectiveness of accounting information systems.